(untitled) (Ustozlar uchun, 2025)
Stress has become a significant concern among university students due to increasing academic demands and life responsibilities. This article explores the major causes of stress among university students, including academic pressure, financial difficulties, time management challenges, and social expectations. It also examines the effects of stress on students’ mental health, academic performance, and physical well-being. Understanding these factors is essential for developing effective strategies to reduce stress and promote a healthier learning environment in higher education institutions.